A wear-resistant and high-temperature resistant plastic lining material and a preparation method thereof

By using PE resin, polyurethane resin and metallic carbon black masterbatch in the lining material, combined with high-speed medium mixer and twin-screw extrusion and other processes, a wear-resistant and high-temperature lining material was prepared, which solved the problem of insufficient performance of existing materials in high-temperature environments and achieved significant improvement in the material's performance.

CN116376133BActive Publication Date: 2025-04-04RUITANG PLASTIC GROUP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211715774.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-04-04
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

The existing lining materials cannot meet the requirements of use in high-temperature environments, especially in terms of anti-aging properties and high-temperature resistance.

Method used

A wear-resistant and high-temperature-resistant plastic lining material is used, and its composition includes PE resin, polyurethane resin, silane coupling agent, supplementary filler, crosslinking agent and metallic carbon black masterbatch. Plastic lining materials with excellent wear and high temperature resistance are prepared by specific process steps such as high-speed medium mixer mixing, twin-screw extrusion and grinding.

Benefits of technology

This material exhibits good wear resistance and high temperature resistance in high temperature environments, avoiding the problems of high self-polymerization of carbon black and poor compatibility between metal and resin, and significantly improving the overall performance of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the field of lining plastic materials, and discloses a wear-resistant and high-temperature resistant lining plastic material and a preparation method thereof. The lining plastic material disclosed in the present invention comprises the following components in parts by weight: 70-95 parts of PE resin, 5-15 parts of polyurethane resin, 10-16 parts of metallic carbon black masterbatch, 5-20 parts of silane coupling agent, 1-8 parts of supplementary filler, 1-3 parts of cross-linking agent, 2-5 parts of auxiliary cross-linking agent, and 1.4-8 parts of processing aid. The lining plastic material provided by the present invention uses PE resin as a matrix resin material, which itself has certain wear resistance and heat aging resistance, and by adding 3-6 parts of metallic carbon black masterbatch, its wear resistance and high temperature resistance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of plastic lining materials, and in particular to a wear-resistant and high-temperature resistant plastic lining material and a preparation method thereof. Background Art

[0002] Lined plastic products are made of metal as the base medium, with excellent thermoplastic materials lined on the inner or outer surface. After lining or rotational molding, they maintain good metal mechanical properties while having the chemical resistance of plastics. For example, metal is combined with lining plastic materials, such as metal and PE resin, to form lining sheets or pipes.

[0003] The existing lining materials can still meet the requirements in normal use, but their performance cannot meet the requirements in specific use environments. When the lining sheet or pipe is used in a high temperature environment, the anti-aging performance and high temperature resistance determined by the resin itself cannot meet the requirements.

[0004] The Chinese patent application publication number CN109485981A discloses a steel-lined plastic fluoroplastic material and its preparation method. The disclosed steel-lined plastic fluoroplastic material has the characteristics of good processing fluidity and stable performance. Its raw materials include: 100 parts of ethylene-tetrafluoroethylene copolymer, 0.5-3 parts of heat stabilizer, 1-3 parts of cross-linking agent, 0.5-1 parts of modified graphene, 10-20 parts of filler, 1-5 parts of impact modifier, and 1-5 parts of dispersant. However, its high temperature resistance still cannot meet the requirements of high temperature operation.

[0005] Therefore, there is an urgent need to develop a new high-temperature resistant plastic lining material that can adapt to specific occasions such as high-temperature operations and meet the needs of production operations within the industry. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a wear-resistant and high-temperature resistant plastic lining material and a preparation method thereof.

[0007] The specific technical scheme of the present invention is:

[0008] On the one hand, the present invention provides a wear-resistant and high-temperature resistant plastic lining material, comprising the following components in parts by weight: 70-95 parts of PE resin, 5-15 parts of polyurethane resin, 5-20 parts of silane coupling agent, 1-8 parts of supplementary filler, 1-3 parts of cross-linking agent, 2-5 parts of auxiliary cross-linking agent, and 1.4-8 parts of processing aid.

[0009] Specifically, the components of the lining plastic material also include metallic carbon black masterbatch, and the mass ratio of the metallic carbon black masterbatch to the PE resin is 10-16:70-95.

[0010] In the wear-resistant and high-temperature resistant plastic lining material of the present invention, PE resin is used as the base resin material, which itself has certain wear resistance and heat aging resistance. The cross-linked plastic lining material prepared by the method provided by the present invention by adding 70-95 parts of PE resin has good high-temperature resistance. Adding 5-15 parts of polyurethane resin can further effectively improve the tear resistance and wear resistance of the plastic lining material.

[0011] In addition, the present invention also provides a metallic carbon black masterbatch, and the wear resistance and high temperature resistance of the lining plastic material can be further improved by adding 3-6 parts of metallic carbon black masterbatch. In the lining plastic material, adding metallic zinc and carbon black is beneficial to improving the wear resistance and high temperature resistance of the material. Carbon black is added to the polymer matrix in the form of particles. It is difficult to disperse a large amount of carbon black well, and it is difficult to ensure the uniform dispersion of carbon black. In the finished lining plastic material, if the carbon black is uneven, it will cause undesirable consequences such as easy cracking. Metallic zinc is a metal material. If it is directly added, due to its poor compatibility with PE resin, the high temperature resistance of the obtained lining plastic material will not only not be improved, but will have a counter-effect of decreasing. In the metallic carbon black masterbatch provided by the present invention, its main active components are metallic zinc and carbon black. Adding metallic zinc and carbon black in the form of metallic carbon black masterbatch is beneficial to improving the compatibility between metal and PE resin and improving the high self-polymerization performance of carbon black. Polyurethane resin has a good matching effect with the metallic carbon black masterbatch provided by the present application as a reinforcing resin.

[0012] Specifically, the present invention provides a method for preparing a metallic carbon black masterbatch, comprising the following steps:

[0013] (1) adding 37 wt % formaldehyde solution to carbon black, adding NaOH to adjust the pH to 8.0-10.3, and reacting at 60-70° C. for 2-3 h to obtain reactive carbon black;

[0014] (2) γ-pyrone, ethyl acetate, and N,N-dimethylacetamide were mixed and dissolved in a mass volume ratio of (1-1.6 g):(15-18 mL):5 mL, and stirred for 1-1.5 h to obtain a ligand solution;

[0015] (3) Put Zn(NO 3 ) 2 6H 2O is dispersed in ethanol at a ratio of 1-1.05 g to 70 mL, reactive carbon black is added, ultrasonic treatment is performed for 20-30 min, ligand solution is added, stirring is performed at 65-75 ° C for 2-4 h, p-xylylenediamine solution is added, the mass ratio of Zn2+ ethanol solution, reactive carbon black, ligand solution and p-xylylenediamine solution is 1:3-4:2-3:0.5-0.7, the temperature is raised to 120-135 ° C and stirred for 3-4.5 h to obtain a metal-carbon black composite; the metal-carbon black composite is added to a mixed solution of styrene monomer and diisopropylbenzene peroxide at a mass ratio of 6-7:4-5.5:1, the mixture is kept warm at 75-85 ° C for 16-20 h, cooled, dried and crushed to obtain a metallic carbon black masterbatch.

[0016] In the process of preparing the fixed carbon black masterbatch provided by the present invention, step (1) is to add carbon black into formaldehyde solution to react and prepare surface hydroxymethylated carbon black, i.e. reactive carbon black, in preparation for connecting with metal in step (3). Step (2) is to prepare ligand solution, which is the basis for connecting dispersed metal. Step (3) is to prepare Zn 2+ As the skeleton core, γ-pyrone and ethyl acetate are used as ligands for complexation, and the carbon black is dispersed and "isolated" during the complexation to form a Zn 2+ The carbon black is fixed and dispersed in a metal frame with the metal as the core, and then p-xylylenediamine is added for cross-linking and curing to form a metal-carbon black composite in which zinc metal and carbon black are mutually dispersed. Styrene monomer and initiator diisopropylbenzene peroxide are added for polymerization, and the carbon black is further dispersed along the porous framework structure of the metal-carbon black composite. The prepared metallic carbon black masterbatch has excellent dispersion effect when used, avoiding the problem of self-polymerization of ordinary carbon black during use that causes material performance to deteriorate.

[0017] Preferably, the PE resin is LDPE resin or / and LLDPE resin.

[0018] Preferably, the density of LDPE resin is 0.92-0.933 g / cm 3 , its melt index at 190°C and 2.16kg load is 2.5-50g / 10min;

[0019] Preferably, the density of LLDPE resin is 0.915-0.935 g / cm 3 , and its melt index of LLDPE resin at 190°C and 2.16kg load is 2.0-20g / 10min.

[0020] Preferably, the polyurethane is a polyether polyurethane or / and a polyester polyurethane. Due to the presence of oxygen-containing groups on the polyurethane, it has a good matching effect with the metallic carbon black masterbatch prepared in the present application.

[0021] Specifically, the supplementary filler is one or more of calcium carbonate, talc and barium sulfate.

[0022] Specifically, the processing aid is one or more of an antioxidant, a heat stabilizer, a light stabilizer, a defoamer and a plasticizer.

[0023] Specifically, the cross-linking agent is one or more of BPO, BPDH and HMMM, and the auxiliary cross-linking agent is one or more of DTBP, PL400 and TAIC.

[0024] On the other hand, the present invention also provides a method for preparing a wear-resistant and high-temperature resistant plastic lining material, comprising the following steps:

[0025] S1: PE resin, polyurethane, silane coupling agent, supplementary filler and processing aid are added to a high-speed intermediate mixer and mixed evenly; then extruded through a twin-screw extruder, the feeding speed of the twin-screw extruder is: 15Hz, the temperature of the control zone is: 90℃-230℃, the melt pressure is: ≤5MPa, the traction speed is 350-800r / min, and the premix is ​​obtained by water cooling, drying and pelletizing after the extrusion of the spline.

[0026] S2: The premix is ​​crushed into powder by a grinder to obtain a premix powder. The grinder parameters are: grinding disc teeth 360-640 teeth, grinding disc gap 20-60 wires, single-layer screen 10-50 mesh.

[0027] S3: Add the cross-linking agent, auxiliary cross-linking agent and metallic carbon black masterbatch to the premixed powder and add them into the heating mixing container equipment, heat to 60℃-70℃ and keep warm for 4-8h, and cool to obtain the wear-resistant and high temperature resistant plastic lining material.

[0028] Compared with the prior art, the present invention has the following technical effects:

[0029] (1) The present invention adds a certain amount of metal zinc and carbon black to prepare a lining plastic material having excellent properties of wear resistance and high temperature resistance.

[0030] (2) The present invention prepares metallic carbon black masterbatch from metallic zinc and carbon black and adds it to the material, thereby effectively solving the problem of uneven dispersion caused by high self-aggregation of carbon black in the resin.

[0031] (3) The present invention effectively solves the problem of poor compatibility of metal in resin by preparing metallic zinc and carbon black into metallic carbon black masterbatch and adding it to the material. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with the embodiments.

[0033] Example 1

[0034] Preparation of metallic carbon black masterbatch:

[0035] (1) adding 37 wt % formaldehyde solution to carbon black, adding NaOH to adjust the pH to 9.0, and reacting at 65° C. for 3 h to obtain reactive carbon black;

[0036] (2) γ-pyrone, ethyl acetate, and N,N-dimethylacetamide were mixed and dissolved in a mass volume ratio of 1.5 g:16 mL:5 mL, and stirred for 1.2 h to obtain a ligand solution;

[0037] (3) Put Zn(NO 3 ) 2 6H 2 O was dispersed in ethanol at a ratio of 1.05 g:70 mL, reactive carbon black was added, ultrasonic treatment was performed for 25 min, ligand solution was added, stirring was performed at 70 °C for 3 h, p-xylylenediamine solution was added, Zn 2+ The mass ratio of ethanol solution, reactive carbon black, ligand solution and para-xylene diamine solution is 1:3:2:0.6, the temperature is raised to 125°C and stirred for 3.5 hours to obtain a metal-carbon black composite; the metal-carbon black composite is added to a mixed solution of styrene monomer and diisopropylbenzene peroxide at a mass ratio of 6:5:1, the mixture is kept warm at 80°C for 18 hours, cooled, dried and crushed to obtain a metallic carbon black masterbatch.

[0038] Preparation of wear-resistant and high temperature resistant plastic lining materials:

[0039] Raw materials: 85 parts of LDPE resin, 10 parts of polyether polyurethane, 14 parts of metallic carbon black masterbatch, 15 parts of vinyl triethoxysilane, 4 parts of antioxidant 300, 4 parts of light stabilizer, 2 parts of BPO, 3 parts of DTBP, and 5 parts of calcium carbonate. The density of LDPE resin is 0.92g / cm 3 , and its melt index at 190°C and 2.16 kg load is 50 g / 10 min.

[0040] S1: PE resin, polyurethane, silane coupling agent, supplementary filler and processing aid are added to a high-speed medium mixer and mixed evenly; then extruded through a twin-screw extruder, the feeding speed of the twin-screw extruder is: 15Hz, the temperature of the control zone is: 90℃-230℃, the melt pressure is: 5MPa, the traction speed is 600r / min, and the sample strips are water-cooled, dried, and pelletized after extrusion to obtain a premix.

[0041] S2: The premix is ​​crushed into powder by a grinder to obtain a premix powder. The grinder parameters are: the number of teeth of the grinding disc is 500, the gap between the grinding disc is 40 wires, and the single-layer screen is 30 meshes.

[0042] S3: Add the cross-linking agent, auxiliary cross-linking agent and metallic carbon black masterbatch to the premixed powder and add them into the heating mixing container equipment, heat to 65°C and keep warm for 6 hours, and cool to obtain the wear-resistant and high-temperature resistant plastic lining material.

[0043] Example 2

[0044] Preparation of metallic carbon black masterbatch:

[0045] (1) adding 37 wt % formaldehyde solution to carbon black, adding NaOH to adjust the pH to 8.0, and reacting at 60° C. for 2 h to obtain reactive carbon black;

[0046] (2) γ-pyrone, ethyl acetate, and N,N-dimethylacetamide were mixed and dissolved in a mass volume ratio of 1 g:15 mL:5 mL, and stirred for 1 h to obtain a ligand solution;

[0047] (3) Put Zn(NO 3 ) 2 6H 2 O was dispersed in ethanol at a ratio of 1 g:70 mL, reactive carbon black was added, ultrasonic treatment was performed for 20 min, ligand solution was added, stirring was performed at 65 °C for 2 h, p-xylylenediamine solution was added, Zn 2+ The mass ratio of ethanol solution, reactive carbon black, ligand solution and para-xylene diamine solution is 1:3:2:0.5, the temperature is raised to 120°C and stirred for 3 hours to obtain a metal-carbon black composite; the metal-carbon black composite is added to a mixed solution of styrene monomer and diisopropylbenzene peroxide at a mass ratio of 6:4:1, the mixture is kept warm at 75°C for 20 hours, cooled, dried and crushed to obtain a metallic carbon black masterbatch.

[0048] Preparation of wear-resistant and high temperature resistant plastic lining materials:

[0049] Raw materials: LLDPE resin 70 parts, polyester polyurethane 5 parts, metallic carbon black masterbatch 10 parts, vinyl triethoxysilane 5 parts, antioxidant AT 10 6 parts, BPO 1 part, DTBP 2 parts, barium sulfate 1.4 parts. The density of LLDPE resin is 0.92g / cm 3 , and its melt index at 190°C and 2.16kg load is 2.0-20g / 10min.

[0050] S1: PE resin, polyurethane, silane coupling agent, supplementary filler and processing aid are added to a high-speed intermediate mixer and mixed evenly; then extruded through a twin-screw extruder, the feeding speed of the twin-screw extruder is: 15Hz, the temperature of the control zone is: 90℃-230℃, the melt pressure is: ≤5MPa, the traction speed is 350-800r / min, and the premix is ​​obtained by water cooling, drying and pelletizing after the extrusion of the spline.

[0051] S2: The premix is ​​crushed into powder by a grinder to obtain a premix powder. The grinder parameters are: the number of teeth of the grinding disc is 640 teeth, the gap between the grinding discs is 60 wires, and the single-layer screen is 50 meshes.

[0052] S3: Add the cross-linking agent, auxiliary cross-linking agent and metallic carbon black masterbatch into the premixed powder and add them into the heating mixing container equipment, heat to 60℃ and keep warm for 8h, and cool to obtain the wear-resistant and high temperature resistant plastic lining material.

[0053] Example 3

[0054] Preparation of metallic carbon black masterbatch:

[0055] (1) adding 37 wt % formaldehyde solution to carbon black, adding NaOH to adjust the pH to 10.3, and reacting at 70° C. for 2 h to obtain reactive carbon black;

[0056] (2) γ-pyrone, ethyl acetate, and N,N-dimethylacetamide were mixed and dissolved in a mass volume ratio of 1.6 g:18 mL:5 mL, and stirred for 1.5 h to obtain a ligand solution;

[0057] (3) Put Zn(NO 3 ) 2 6H 2 O was dispersed in ethanol at a ratio of 1 g:70 mL, reactive carbon black was added, ultrasonic treatment was performed for 30 min, ligand solution was added, stirred at 75 °C for 4 h, p-xylylenediamine solution was added, Zn 2+ The mass ratio of ethanol solution, reactive carbon black, ligand solution and paraxylene diamine solution is 1:4:3:0.7, the temperature is raised to 135°C and stirred for 4.5 hours to obtain a metal-carbon black composite; the metal-carbon black composite is added to a mixed solution of styrene monomer and diisopropylbenzene peroxide at a mass ratio of 7:5.5:1, the mixture is kept at 85°C for 20 hours, cooled, dried and crushed to obtain a metallic carbon black masterbatch.

[0058] Preparation of wear-resistant and high temperature resistant plastic lining materials:

[0059] Raw materials: 95 parts of LDPE resin, 15 parts of polyether polyurethane, 16 parts of metallic carbon black masterbatch, 20 parts of vinyl triethoxysilane, 2 parts of antioxidant 300, 3 parts of BPO, 5 parts of DTBP, and 8 parts of talc. The density of LDPE resin is 0.933g / cm 3, and its melt index at 190°C and 2.16kg load is 2.5g / 10min S1: PE resin, polyurethane, silane coupling agent, supplementary filler, and processing aid are added to a high-speed medium mixer and mixed evenly; then extruded through a twin-screw extruder, the feeding speed of the twin-screw extruder is: 15Hz, the temperature in the control zone is: 90°C-230°C, the melt pressure is: ≤5MPa, the traction speed is 350-800r / min, and the spline is extruded and water-cooled, dried, and pelletized to obtain a premix.

[0060] S2: The premix is ​​crushed into powder by a grinder to obtain a premix powder. The grinder parameters are: 360 teeth of the grinding disc, 20 wires of the grinding disc gap, and 10 meshes of the single-layer screen.

[0061] S3: Add the cross-linking agent, auxiliary cross-linking agent and metallic carbon black masterbatch to the premixed powder and add them into the heating mixing container equipment, heat to 70°C and keep warm for 4 hours, and cool to obtain the wear-resistant and high-temperature resistant plastic lining material.

[0062] Example 4

[0063] Preparation of wear-resistant and high temperature resistant plastic lining materials:

[0064] Raw materials: 85 parts of LDPE resin, 10 parts of polyether polyurethane, 15 parts of vinyl triethoxysilane, 10 parts of masterbatch, 4 parts of antioxidant 300, 4 parts of light stabilizer, 2 parts of BPO, 3 parts of DTBP, 5 parts of calcium carbonate. The density of LDPE resin is 0.92g / cm 3 , and its melt index at 190°C and 2.16 kg load is 50 g / 10 min.

[0065] S1: PE resin, polyurethane, silane coupling agent, supplementary filler and processing aid are added to a high-speed medium mixer and mixed evenly; then extruded through a twin-screw extruder, the feeding speed of the twin-screw extruder is: 15Hz, the temperature of the control zone is: 90℃-230℃, the melt pressure is: 5MPa, the traction speed is 600r / min, and the sample strips are water-cooled, dried, and pelletized after extrusion to obtain a premix.

[0066] S2: The premix is ​​crushed into powder by a grinder to obtain a premix powder. The grinder parameters are: the number of teeth of the grinding disc is 500, the gap between the grinding disc is 40 wires, and the single-layer screen is 30 meshes.

[0067] S3: Add the cross-linking agent and the auxiliary cross-linking agent to the premixed powder and add them into the heating mixing container equipment, heat to 65°C and keep warm for 6 hours, and cool to obtain the wear-resistant and high-temperature resistant lining plastic material.

[0068] Comparative Example 1 (the main difference from Example 1 is that carbon black and metallic zinc are not prepared as metallic carbon black masterbatch) Lining material preparation:

[0069] Raw materials: 85 parts of LDPE resin, 10 parts of polyether polyurethane, 8 parts of carbon black, 3 parts of metal zinc, 15 parts of vinyl triethoxysilane, 4 parts of antioxidant 300, 4 parts of light stabilizer, 2 parts of BPO, 3 parts of DTBP, 5 parts of calcium carbonate. The density of LDPE resin is 0.92g / cm 3 , and its melt index at 190°C and 2.16 kg load is 50 g / 10 min.

[0070] S1: PE resin, polyurethane, silane coupling agent, supplementary filler and processing aid are added to a high-speed medium mixer and mixed evenly; then extruded through a twin-screw extruder, the feeding speed of the twin-screw extruder is: 15Hz, the temperature of the control zone is: 90℃-230℃, the melt pressure is: 5MPa, the traction speed is 600r / min, and the sample strips are water-cooled, dried, and pelletized after extrusion to obtain a premix.

[0071] S2: The premix is ​​crushed into powder by a grinder to obtain a premix powder. The grinder parameters are: the number of teeth of the grinding disc is 500, the gap between the grinding disc is 40 wires, and the single-layer screen is 30 meshes.

[0072] S3: Add the cross-linking agent, auxiliary cross-linking agent and metallic carbon black masterbatch to the premixed powder and add them into a heating mixing container, heat to 65°C and keep warm for 6 hours, and cool to obtain the lining material.

[0073] Comparative Example 2 (the main difference from Example 1 is that carbon black and metal zinc are prepared as a metal-carbon black composite) Preparation of metal-carbon black composite:

[0074] (1) adding 37 wt % formaldehyde solution to carbon black, adding NaOH to adjust the pH to 9.0, and reacting at 65° C. for 3 h to obtain reactive carbon black;

[0075] (2) γ-pyrone, ethyl acetate, and N,N-dimethylacetamide were mixed and dissolved in a mass volume ratio of 1.5 g:16 mL:5 mL, and stirred for 1.2 h to obtain a ligand solution;

[0076] (3) Put Zn(NO 3 ) 2 6H 2 O was dispersed in ethanol at a ratio of 1.05 g:70 mL, reactive carbon black was added, ultrasonic treatment was performed for 25 min, ligand solution was added, stirring was performed at 70 °C for 3 h, p-xylylenediamine solution was added, Zn 2+ The mass ratio of ethanol solution, reactive carbon black, ligand solution and p-xylylenediamine solution is 1:3:2:0.6, the temperature is raised to 125° C. and stirred for 3.5 hours to obtain a metal-carbon black composite, which is then dried and crushed to obtain a metal-carbon black composite.

[0077] Preparation of plastic lining materials:

[0078] Raw materials: 85 parts of LDPE resin, 10 parts of polyether polyurethane, 14 parts of metal-carbon black compound, 15 parts of vinyl triethoxysilane, 4 parts of antioxidant 300, 4 parts of light stabilizer, 2 parts of BPO, 3 parts of DTBP, and 5 parts of calcium carbonate. The density of LDPE resin is 0.92g / cm 3 , and its melt index at 190°C and 2.16 kg load is 50 g / 10 min.

[0079] S1: PE resin, polyurethane, silane coupling agent, supplementary filler and processing aid are added to a high-speed medium mixer and mixed evenly; then extruded through a twin-screw extruder, the feeding speed of the twin-screw extruder is: 15Hz, the temperature of the control zone is: 90℃-230℃, the melt pressure is: 5MPa, the traction speed is 600r / min, and the sample strips are water-cooled, dried, and pelletized after extrusion to obtain a premix.

[0080] S2: The premix is ​​crushed into powder by a grinder to obtain a premix powder. The grinder parameters are: the number of teeth of the grinding disc is 500, the gap between the grinding disc is 40 wires, and the single-layer screen is 30 meshes.

[0081] S3: Add the cross-linking agent, auxiliary cross-linking agent and metal-carbon black composite to the premixed powder, add the mixture into a heating mixing container, heat to 65°C and keep warm for 6 hours, and cool to obtain the lining material.

[0082] Comparative Example 3 (the main difference from Example 1 is that the metallic carbon black masterbatch is added in step S1)

[0083] Preparation of metallic carbon black masterbatch:

[0084] (1) adding 37 wt % formaldehyde solution to carbon black, adding NaOH to adjust the pH to 9.0, and reacting at 65° C. for 3 h to obtain reactive carbon black;

[0085] (2) γ-pyrone, ethyl acetate, and N,N-dimethylacetamide were mixed and dissolved in a mass volume ratio of 1.5 g:16 mL:5 mL, and stirred for 1.2 h to obtain a ligand solution;

[0086] (3) Put Zn(NO 3 ) 2 6H 2 O was dispersed in ethanol at a ratio of 1.05 g:70 mL, reactive carbon black was added, ultrasonic treatment was performed for 25 min, ligand solution was added, stirring was performed at 70 °C for 3 h, p-xylylenediamine solution was added, Zn 2+The mass ratio of ethanol solution, reactive carbon black, ligand solution and para-xylene diamine solution is 1:3:2:0.6, the temperature is raised to 125°C and stirred for 3.5 hours to obtain a metal-carbon black composite; the metal-carbon black composite is added to a mixed solution of styrene monomer and diisopropylbenzene peroxide at a mass ratio of 6:5:1, the mixture is kept warm at 80°C for 18 hours, cooled, dried and crushed to obtain a metallic carbon black masterbatch.

[0087] Preparation of plastic lining materials:

[0088] Raw materials: 85 parts of LDPE resin, 10 parts of polyether polyurethane, 14 parts of metallic carbon black masterbatch, 15 parts of vinyl triethoxysilane, 4 parts of antioxidant 300, 4 parts of light stabilizer, 2 parts of BPO, 3 parts of DTBP, and 5 parts of calcium carbonate. The density of LDPE resin is 0.92g / cm 3 , and its melt index at 190°C and 2.16 kg load is 50 g / 10 min.

[0089] S1: PE resin, polyurethane, silane coupling agent, supplementary filler, processing aid, metallic carbon black masterbatch are added to a high-speed medium mixer and mixed evenly; then extruded through a twin-screw extruder, the feeding speed of the twin-screw extruder is: 15Hz, the temperature of the control zone is: 90℃-230℃, the melt pressure is: 5MPa, the traction speed is 600r / min, and the sample strips are water-cooled, dried, and pelletized to obtain a premix after extrusion.

[0090] S2: The premix is ​​crushed into powder by a grinder to obtain a premix powder. The grinder parameters are: the number of teeth of the grinding disc is 500, the gap between the grinding disc is 40 wires, and the single-layer screen is 30 meshes.

[0091] S3: Add the cross-linking agent and the auxiliary cross-linking agent to the premixed powder and add the mixture into a heating mixing container, heat to 65°C and keep warm for 6 hours, and cool to obtain the lining plastic material.

[0092] Comparative Example 4 (the main difference from Example 1 is that no polyether polyurethane is added)

[0093] Preparation of metallic carbon black masterbatch:

[0094] (1) adding 37 wt % formaldehyde solution to carbon black, adding NaOH to adjust the pH to 9.0, and reacting at 65° C. for 3 h to obtain reactive carbon black;

[0095] (2) γ-pyrone, ethyl acetate, and N,N-dimethylacetamide were mixed and dissolved in a mass volume ratio of 1.5 g:16 mL:5 mL, and stirred for 1.2 h to obtain a ligand solution;

[0096] (3) Put Zn(NO 3 ) 2 6H 2O was dispersed in ethanol at a ratio of 1.05 g:70 mL, reactive carbon black was added, ultrasonic treatment was performed for 25 min, ligand solution was added, stirring was performed at 70 °C for 3 h, p-xylylenediamine solution was added, Zn 2+ The mass ratio of ethanol solution, reactive carbon black, ligand solution and para-xylene diamine solution is 1:3:2:0.6, the temperature is raised to 125°C and stirred for 3.5 hours to obtain a metal-carbon black composite; the metal-carbon black composite is added to a mixed solution of styrene monomer and diisopropylbenzene peroxide at a mass ratio of 6:5:1, the mixture is kept warm at 80°C for 18 hours, cooled, dried and crushed to obtain a metallic carbon black masterbatch.

[0097] Preparation of plastic lining materials:

[0098] Raw materials: 85 parts of LDPE resin, 10 parts of polyether polyurethane, 14 parts of metallic carbon black masterbatch, 15 parts of vinyl triethoxysilane, 4 parts of antioxidant 300, 4 parts of light stabilizer, 2 parts of BPO, 3 parts of DTBP, and 5 parts of calcium carbonate. The density of LDPE resin is 0.92g / cm 3 , and its melt index at 190°C and 2.16 kg load is 50 g / 10 min.

[0099] S1: PE resin, polyether polyurethane, silane coupling agent, supplementary filler and processing aid are added to a high-speed medium mixer and mixed evenly; then extruded through a twin-screw extruder, the feeding speed of the twin-screw extruder is: 15Hz, the temperature of the control zone is: 90℃-230℃, the melt pressure is: 5MPa, the traction speed is 600r / min, and the sample strips are water-cooled, dried, and pelletized after extrusion to obtain a premix.

[0100] S2: The premix is ​​crushed into powder by a grinder to obtain a premix powder. The grinder parameters are: the number of teeth of the grinding disc is 500, the gap between the grinding disc is 40 wires, and the single-layer screen is 30 meshes.

[0101] S3: Add the cross-linking agent, auxiliary cross-linking agent and metallic carbon black masterbatch to the premixed powder and add them into a heating mixing container, heat to 65°C and keep warm for 6 hours, and cool to obtain the lining material.

[0102] Comparative Example 5 (the main difference from Example 1 is that 20 parts of polyether polyurethane are added)

[0103] Preparation of metallic carbon black masterbatch:

[0104] (1) adding 37 wt % formaldehyde solution to carbon black, adding NaOH to adjust the pH to 9.0, and reacting at 65° C. for 3 h to obtain reactive carbon black;

[0105] (2) γ-pyrone, ethyl acetate, and N,N-dimethylacetamide were mixed and dissolved in a mass volume ratio of 1.5 g:16 mL:5 mL, and stirred for 1.2 h to obtain a ligand solution;

[0106] (3) Put Zn(NO 3 ) 2 6H 2 O was dispersed in ethanol at a ratio of 1.05 g:70 mL, reactive carbon black was added, ultrasonic treatment was performed for 25 min, ligand solution was added, stirring was performed at 70 °C for 3 h, p-xylylenediamine solution was added, Zn 2+ The mass ratio of ethanol solution, reactive carbon black, ligand solution and para-xylene diamine solution is 1:3:2:0.6, the temperature is raised to 125°C and stirred for 3.5 hours to obtain a metal-carbon black composite; the metal-carbon black composite is added to a mixed solution of styrene monomer and diisopropylbenzene peroxide at a mass ratio of 6:5:1, the mixture is kept warm at 80°C for 18 hours, cooled, dried and crushed to obtain a metallic carbon black masterbatch.

[0107] Preparation of wear-resistant and high temperature resistant plastic lining materials:

[0108] Raw materials: 85 parts of LDPE resin, 20 parts of polyether polyurethane, 14 parts of metallic carbon black masterbatch, 15 parts of vinyl triethoxysilane, 4 parts of antioxidant 300, 4 parts of light stabilizer, 2 parts of BPO, 3 parts of DTBP, and 5 parts of calcium carbonate. The density of LDPE resin is 0.92g / cm 3 , and its melt index at 190°C and 2.16 kg load is 50 g / 10 min.

[0109] S1: PE resin, polyether polyurethane, silane coupling agent, supplementary filler and processing aid are added to a high-speed medium mixer and mixed evenly; then extruded through a twin-screw extruder, the feeding speed of the twin-screw extruder is: 15Hz, the temperature of the control zone is: 90℃-230℃, the melt pressure is: 5MPa, the traction speed is 600r / min, and the sample strips are water-cooled, dried, and pelletized after extrusion to obtain a premix.

[0110] S2: The premix is ​​crushed into powder by a grinder to obtain a premix powder. The grinder parameters are: the number of teeth of the grinding disc is 500, the gap between the grinding disc is 40 wires, and the single-layer screen is 30 meshes.

[0111] S3: Add the cross-linking agent, auxiliary cross-linking agent and metallic carbon black masterbatch to the premixed powder and add them into a heating mixing container, heat to 65°C and keep warm for 6 hours, and cool to obtain the lining material.

[0112] Performance Testing

[0113] The lining plastic materials prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were molded and tested for performance, and the test results are shown in Table 1. The high temperature resistance test method is: the test material is tested for cracking after being heat aged at 135°C in an air oven for 720 hours, and no cracking is recorded as passing, and cracking is recorded as failing.

[0114] Table 1

[0115] Tensile strength(MPa) Heat deformation temperature(℃) High temperature resistance test Example 1 56 305 pass Example 2 54 295 pass Example 3 55 300 pass Example 4 49 290 pass Comparative Example 1 42 240 Not passed Comparative Example 2 45 290 pass Comparative Example 3 45 245 Not passed Comparative Example 4 41 240 Not passed Comparative Example 5 48 290 pass

[0116] Data analysis

[0117] (1) As shown in Table 1, the lining plastic materials prepared in Examples 1 to 4 have excellent wear resistance and high temperature resistance.

[0118] (2) Compared with Example 1, in Comparative Example 1, carbon black and metallic zinc are not prepared as metallic carbon black masterbatch but are directly added. The mechanical strength and high temperature resistance of the carbon black and metallic zinc are reduced, indicating that the addition of carbon black and metallic zinc alone is not conducive to the improvement of their performance. Further analysis shows that the reason may be the uneven dispersion of carbon black and / or the poor compatibility of metallic zinc with the resin.

[0119] (3) Compared with Example 1, the carbon black and metal zinc in Comparative Example 2 were prepared into a metal-carbon black composite, which passed the high temperature resistance test, but the wear resistance decreased, indicating that further preparing the metal-carbon black composite into a metallic carbon black masterbatch is beneficial to improving the wear resistance of the material.

[0120] (4) Compared with Example 1, in Comparative Example 3, the metallic carbon black masterbatch was added in step S1, and its mechanical strength decreased, and it failed the high temperature resistance test, indicating that the metallic carbon black masterbatch needs to be added and mixed after extrusion, otherwise it will affect its effect.

[0121] (5) Compared with Example 1, the mechanical strength of Comparative Example 4 was deteriorated without adding polyether polyurethane, and it failed the high temperature resistance test, indicating that adding a certain amount of polyurethane resin is beneficial to improving the wear resistance and high temperature resistance of the material.

[0122] (6) Compared with Example 1, in Example 5, 20 parts of polyether polyurethane were added. Too much polyurethane resin was added, and its mechanical strength decreased. This shows that polyurethane resin is not conducive to improving the wear resistance of the material. The addition amount of polyurethane resin should be within an appropriate range.

[0123] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0124] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a wear-resistant and high-temperature resistant plastic lining material, characterized in that: The following steps are involved: S1: 70-95 parts of PE resin, 5-15 parts of polyurethane, 5-20 parts of silane coupling agent, 1-8 parts of supplementary filler, and 1.4-8 parts of processing aid are mixed, extruded, water-cooled, dried, and pelletized to obtain a premix; S2: crushing the premix into powder to obtain a premix powder; S3: adding 1-3 parts of a cross-linking agent, 2-5 parts of a co-cross-linking agent and 10-16 parts of a metallic carbon black masterbatch to the premixed powder, mixing evenly, heating and heat preservation, and cooling to obtain a wear-resistant and high temperature resistant plastic lining material; Metallic carbon black masterbatch is prepared by adding carbon black into formaldehyde solution to react and obtain reactive carbon black. 2+ As the skeleton core, γ-pyrone and ethyl acetate are used as ligands for complexation to form a Zn 2+ The carbon black is fixed and dispersed in a metal frame with the carbon black as the core; p-xylylenediamine is added for cross-linking and curing, styrene monomer and diisopropylbenzene peroxide are added for polymerization, and the mixture is cooled, dried and crushed to obtain a metallic carbon black masterbatch.

2. The method for preparing a wear-resistant and high-temperature resistant plastic lining material according to claim 1, characterized in that: The preparation of the metallic carbon black masterbatch comprises the following steps: (1) Adding formaldehyde solution to carbon black to obtain reactive carbon black; (2) Mixing and dissolving γ-pyrone, ethyl acetate, and N,N-dimethylacetamide to obtain a ligand solution; (3) Disperse Zn(NO3)2•6H2O in ethanol, add reactive carbon black, perform ultrasonic treatment, add ligand solution, stir at 65-75°C for 2-4 h, add p-xylylenediamine solution, raise the temperature to 120-135°C and stir for 3-4.5 h to obtain a metal-carbon black complex; add the metal-carbon black complex to a mixed solution of styrene monomer and diisopropylbenzene peroxide, keep the mixture at 75-85°C for 16-20 h, cool, dry and grind to obtain a metallic carbon black masterbatch.

3. The method for preparing a wear-resistant and high-temperature resistant plastic lining material according to claim 2, characterized in that: The γ-pyrone, ethyl acetate, and N,N-dimethylacetamide are mixed and dissolved in a mass volume ratio of (1-1.6 g): (15-18 mL): 5 mL; the Zn(NO3)2•6H2O dispersed in ethanol forms a Zn 2+ The mass ratio of the ethanol solution, the reactive carbon black, the ligand solution and the p-xylylenediamine solution is 1: 3-4: 2-3: 0.5-0.

7.

4. The method for preparing a wear-resistant and high-temperature resistant plastic lining material according to claim 1, characterized in that: The PE resin is LDPE resin and / or LLDPE resin.

5. The method for preparing a wear-resistant and high-temperature resistant plastic lining material according to claim 4, characterized in that: The density of the LDPE resin is 0.92-0.933 g / cm 3 , the melt index of the LDPE resin at 190° C. and 2.16 kg load is 2.5-50 g / 10 min; The density of the LLDPE resin is 0.915-0.935 g / cm 3 The LLDPE resin has a melt index of 2.0-20 g / 10 min at 190° C. and a load of 2.16 kg.

6. The method for preparing a wear-resistant and high-temperature resistant plastic lining material according to claim 1, characterized in that: The polyurethane is polyether polyurethane or / and polyester polyurethane.

7. The method for preparing a wear-resistant and high-temperature resistant plastic lining material according to claim 1, characterized in that: The supplementary filler is one or more of calcium carbonate, talcum powder and barium sulfate.

8. The method for preparing a wear-resistant and high-temperature resistant plastic lining material according to claim 1, characterized in that: The processing aid is one or more of an antioxidant, a heat stabilizer, a light stabilizer, a defoamer and a plasticizer.

9. The method for preparing a wear-resistant and high-temperature resistant plastic lining material according to claim 1, characterized in that: The cross-linking agent is one or more of BPO, BPDH and HMMM.

10. The method for preparing a wear-resistant and high-temperature resistant plastic lining material according to claim 1, characterized in that: The auxiliary cross-linking agent is one or more of DTBP, PL400 and TAIC.

Citation Information

Patent Citations

  • Plastic-lined steel fluoroplastic material and preparation method thereof

    CN109485981A

  • Silane crosslinked polyethylene special-purpose material for internal bladder of electric water heater

    CN101805424A

  • Crosslinked polyethylene rotationally moulded material for water heater inner container and preparation method and applications thereof

    CN109851901A

  • High molecular wear-resistant strip capable of enhancing wear resistance

    CN109942927A

  • Electron irradiation crosslinked polyethylene material and preparation method thereof

    CN113416360A